Effect of temperature and cytokinin on thr capacity of direct somatic embryogenesis in Coffea arabica L. genotypes - Almeida, Julieta Andréa Silva de; Leal, Rebeca Rocha; Carmazini, Valéria Cristina Barbosa; Salomon, Marcus Vinicius; Guerreiro-Filho, Oliveiro (Coffee Science - ISSN 1984-3909, 2014)
The vegetative multiplication of Coffea arabica hybrids can be carried out by direct somatic embryogenesis. The objective of this study was to verify if temperature and cytokinins could influence the capacity for direct somatic embryogeneis in arabica genotypes. For this purpose foliar explants taken from adult plants of three C. arabica genotypes, hybrids 812 and 956 and cultivar Catuaí, were inoculated into a culture medium with ½ MS salts, 20.0 g l-1 sucrose and 30 μM 6-benzyladenine (6-BA) or 10 μM 2-isopenteniladenina (2-iP) and submitted to temperatures of 25 and 30 ºC in the absence of light. The treatments were evaluated with respect to the number of somatic embryos formed per foliar explant, at 270 days after the beginning of the experiment. A completely random experimental design was adopted with a 3 x 2 x 2 (genotype x temperature x plant growth regulator) factorial scheme, with ten replications per treatment and two explants in each. Temperature of 30 oC favored significantly the formation of somatic embryos when compared to 25 oC and this response pattern predominated amongst the three genotypes. On the other hand, 6-BA and 2-iso-pentenladenine caused similar answers for the majority of genotypes. The results of this study showed that temperature has a significant influence on the direct somatic embryogenesis capacity of C. arabica genotypes. <!--[endif] -->